2018
DOI: 10.1167/iovs.17-23159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ERK1/2 Activation in Sarpogrelate-Mediated Neuroprotection

Abstract: PurposeTo characterize the mediators of 5-HT2A serotonin receptor–driven retinal neuroprotection.MethodsAlbino mice were treated intraperitoneally with saline or sarpogrelate, a 5-HT2A antagonist, immediately before light exposure (LE). Following LE, retinas were harvested for a high-throughput phosphorylation microarray to quantify activated phosphorylated proteins in G protein–coupled receptor (GPCR) signaling. To confirm microarray results and define temporal changes, Western blots of select GPCR signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Western blot was performed as described previously 39. Proteins in the NF-kB and NRF2 pathways were measured in the neural retina, at 1, 3, 6, 12, and 24 hours after LIR.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed as described previously 39. Proteins in the NF-kB and NRF2 pathways were measured in the neural retina, at 1, 3, 6, 12, and 24 hours after LIR.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, in a light-induced photoreceptor degeneration model, 15 mg/kg of sarpogrelate treatment (a selective 5-HT2A receptor antagonist) was enough to obtain significant improvement of retinal function in ERG recordings that cannot be observed by OCT. Nevertheless, after a higher dose (40 mg/kg) OCT imaging was able to evidence an increase in ONL thickness (Ku et al, 2018;Tullis et al, 2015). On the other hand, OCT was useful to show the attenuation of neuroprotection when same treatment is combined with ERK1/2 inhibitor, while ERG recordings were not able to show these differences (Ku et al, 2018).…”
Section: Use Of Oct In Experimental Neuroprotectionmentioning
confidence: 99%
“…Nevertheless, after a higher dose (40 mg/kg) OCT imaging was able to evidence an increase in ONL thickness (Ku et al, 2018;Tullis et al, 2015). On the other hand, OCT was useful to show the attenuation of neuroprotection when same treatment is combined with ERK1/2 inhibitor, while ERG recordings were not able to show these differences (Ku et al, 2018).…”
Section: Use Of Oct In Experimental Neuroprotectionmentioning
confidence: 99%
“… 38 , 39 Our work, as well as others, has shown that increases in corticosterone and activation of the MAPK pathway, as well as CREB, can elicit neuroprotective pathways and protect from light-induced retinopathy. 32 , 40 42 In addition to activating a stress response, early weaning can delay the triggering of satiety and modulate the circadian rhythm of food intake, which was demonstrated in male Wistar rat pups out to PD100. 43 It is feasible that changes in behavioral satiety and food consumption can impact the retina, because recent studies have linked the gut microbiota with retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal rhodopsin and β-actin protein content was measured via Western blot at PD40. 32 Total protein was extracted, and 100 µg of protein was loaded into a 4% to 20% tris-glycine gel. After transfer, membranes were blocked for one hour, incubated overnight in primary antibodies (anti-rhodopsin Rho 4D2, ab98887 and anti-actin, ab3280; Abcam, Cambridge, UK), and incubated in a secondary antibody (1:15,000, goat anti-mouse IRDye 800CW, 925-32210; LICOR, Lincoln, NE, USA).…”
Section: Methodsmentioning
confidence: 99%